ANALISIS MODEL TIME SERIES DALAM PERAMALAN JARINGAN BASE TRANSCEIVER STATION (BTS) PER PROVIDER DI KOTA PONTIANAK SAMPAI TAHUN 2025 - Singgih Anggi Purnama . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2016)
Abstract The increasing number of customers and traffic, the network capacity is not enough to meet the needs of customers. For carriers issues must always evaluate capacity of the BTS itself, according to customers growth to determine service capability in the future, then operator should apply the theory of traffic forecasting that would happen even on the next month. Cell phone network infrastructure planning requests minimal cultivated hardware issue yet able to meet as much as possible capacity existing traffic. The vendor in the city of Pontianak until 2015 some 413 vendor consisting of Telkomsel, XL, Indosat and Tri, the number of every base station owned by vendor of Telkomsel with 127 BTS, as many as 67 BTS of XL, Indosat about 103 bts and Tri about 116 BTS. A method of time series based on the assumption that, data has internal structure, as autocorelation, a trend or seasonal variations. The data which is used to research is taken from secondary data and it is covering the number of providers in the city of Pontianak and data population of the 2010 until 2015. And also secondary data of telecommunications providers in the city of pontianak in the form of customer and number of BTS. Based on the calculation BTS  forecasting needs 4 gsm providers in the Pontianak city, note that providers Telkomsel to use its in 2010-2014 were 127 its with average construction of around 25 Bts annually increased to 128 BTS until 2025. The Provider requisite of XL on the use of its in 2010-2014 were 67 Bts with average construction of around 13 BTS annually and it is increasing to 70 BTS until 2025. The requisite of providers Indosat on the use of BTS in 2010-2014 were 103 BTS with average construction of around 21 BTS annually increased to 105 BTS until 2025. Meanwhile, the provider needs to use BTS Tri providers in 2010-2014 amounted to 116 base stations with an average of about 23 BTS development increased to 122 base stations per year until 2025. The need for the network as a whole amounted to 70 base stations BTS and the average requisite of BTS network in Pontianak among 2015-2025 amounted to 18 base stations per year. With a significant number of base stations that should be built every year, otherwise the need for the use of the tower shared indispensable. Keywords: BTS, Provider, Forecasting, Time Series